Between Duty, Capacity, and Inability: Post-Divorce Child Support in Indonesian Religious Courts - Muhsan Syarafuddin; Gioia Beatrice; Ghufran Jauhar; Ghifary Duyufur Rohman; Haris Maiza Putra (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2026)
When the court explicitly acknowledges a father's economic incapacity, child support obligations after divorce create acute legal tension. This article looks at a confusing situation in child support decisions after divorce, based on Decision Number 4501/Pdt.G/2024/PA.Jr. from the Jember Religious Court, Indonesia, where the court required a fixed child support payment even though the father had proven he couldn't afford it. The case highlights a bigger problem that courts face in areas with different laws and economic challenges: how to balance the need to protect children with the reality that some financial obligations may not be possible to enforce. This study uses a legal approach to analyse laws, court decisions, and important Islamic legal sources to assess whether the court's reasoning is fair. The findings reveal a structural inconsistency. Even though the court referenced child protection rules and traditional legal views that support parental responsibility, the maintenance order was too high for the father to afford, making it very difficult for him to follow. Through the evaluative lens of Maqāṣid al-Sharīʿah, the decision demonstrates a failure of proportional balancing: the protection of offspring (ḥifẓ al-nasl) was prioritised without adequate consideration of economic preservation and basic welfare (ḥifẓ al-māl and ḥifẓ al-nafs), both foundational objectives within Islamic legal thought. The article argues that this pattern in court decisions shows a common problem in family courts with limited resources, where the legal responsibilities are recognised more than they can actually be enforced. By placing a local decision within this ongoing issue, the study adds to worldwide discussions about fairness, the ability to enforce choices, and the power of judges in child support cases after divorce.